Enhancing the English Writing Skill Through Active Reading in English Teaching - Sihombing, Marino; Napitupulu, Selviana (Innovative: Journal Of Social Science Research, 2025)
Proficiency in English writing is essential for success in academic, professional, and social contexts. However, many learners face challenges due to traditional teaching methods that often overlook the importance of reading comprehension and critical thinking. This study explores how active reading a deliberate, engaged approach to reading can significantly enhance English writing skills. Strategies such as skimming, scanning, annotating, and note-taking are highlighted for their role in improving comprehension, critical thinking, and writing coherence. Active reading deepens engagement with texts, expands vocabulary, and strengthens analytical skills, which are directly transferable to effective written communication. The evidence from existing literature shows that active reading methods outperform traditional approaches by promoting critical analysis, thoughtful expression, and better organization of ideas. Cognitive techniques like questioning, summarizing, and visualizing further support learners in articulating clear and cohesive writing. The study emphasizes the need for integrating active reading strategies into English teaching practices to address gaps in traditional methods. By equipping students with these tools, educators can enhance writing proficiency, boost engagement, and better prepare learners for global academic and professional challenges. This research underscores the importance of training teachers to implement evidence-based active reading techniques effectively, ensuring long-term benefits for students’ writing success.